Gerakan Literasi Sekolah dan Kemampuan Literasi Siswa di SMA Negeri 3 Salatiga - Nugrohadi, Saptono; Asri, Dail Umamil; Chasanah, Iswatun (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2024)
This study aims to determine and describe the school literacy movement and students' literacy skills. This study is a quantitative descriptive study with the analysis technique used, namely descriptive statistical analysis. The sample in this study were students of SMA Negeri 3 Salatiga Class X, XI and XII, both Language, Science and Social Studies classes, who participated in literacy activities and worked on the test questions given, namely 629 students. The results of this study explain that literacy activities at SMA Negeri 3 Salatiga are carried out routinely every day, namely 10 minutes before learning activities begin. Students are given readings and several test questions to measure students' literacy skills. The results of the analysis show that overall, 36.72% of students scored 83.33, followed by students who scored 66.67 as many as 19.87%. However, there are also quite a few students who scored 0, namely 4.93%, and those who scored 16.67 as many as 12.88%. The feedback that students gave the most was related to readings that could be more varied and interesting, as well as questions that were given that were too long, many and difficult.